Screening for Cushing Syndrome at the Primary Care Level: What Every General Practitioner Must Know - Ernest Yorke; Yacoba Atiase; Josephine Akpalu; Osei Sarfo-Kantanka (International Journal of Endocrinology)
Cushing’s syndrome is a rare entity, and a high index of suspicion is needed for screening in a primary care setting. The clinical awareness of the primary care physician (PCP) to the highly indicative signs and symptoms such as facial plethora, proximal myopathy, reddish purple striae, and easy bruisability should alert him to look for biochemical evidence of Cushing’s syndrome through any of the first-line screening tests, namely, 24-hour urinary free cortisol, overnight dexamethasone suppression test, or late-night salivary cortisol. Commonly used random cortisol measurements are unreliable; hence, general practitioners are encouraged to understand the use of these more reliable tests with increased sensitivity and specificity for screening Cushing’s syndrome. In this write-up, we set out to increase awareness about the presentation of Cushing’s syndrome and current recommended screening methods as well as their strengths and weaknesses. We relied mainly on the recommendations by the Endocrine Society Guidelines.